P1451MONOCYTE/NEUTROPHIL: LYMPHOCYTE RATIO, C-REACTIVE PROTEIN IN THE LAST YEAR BEFORE DEATH IN DIFFERENT VINTAGE GROUPS - RESULTS FROM THE MONDO INITIATIVE. (6th June 2020) - Ye, Xiaoling; Bright, Rupert; Woollard, Kevin; Pusey, Charles Dickson; Duncan, Neill; Kotanko, Peter
Abstract: Background and Aims: Both experimental and clinical evidence have indicated the relationship between chronic inflammation and adverse outcomes in dialysis patients. It is also well know that higher white blood cell counts and their subtypes including monocyte and neutrophil counts, as well as higher neutrophil to lymphocyte ration (NLR) and monocyte to lymphocyte ration (MLR), and C-reactive protein (CRP) are related to inflammation, and higher risk of access failure, hospitalizations and death in dialysis patients. However, little has been done to explore the characteristics for each of these markers for patients with different dialysis vintage in a large sample of cohorts. Method: Four time periods were identified: a) acute phase - patients who died within the 1 years on dialysis, b) early-stable phase - patients who died within the 2 nd year on dialysis, c) mid-stable phase – died on the 3 rd year on dialysis, and 4) late-stable phase – died on the 4 th year on dialysis. All-cause mortality was recorded during the 4 studied periods. Patients with at least one monocyte count, neutrophil count, and lymphocyte count during each of the study period were included. Cubic spline functions were applied to plot the trends of neutrophil counts, monocyte counts, lymphocyte counts, MLR, NLR and CRP with month 0 being the month of the event death and counting backward until the 12 months preceding to death for the 4 studied phases. Rate of change functions were also built to study the accelerating and decelerating changes of the trends within the 12 months preceding death for each of the inflammatory markers. Results: A total of 2, 504 patients were included in acute phase analysis; 1, 696 in the early-stable phase analysis, 1, 462 patients in the mid-stable analysis, and 1, 305 patients in the late-stable phase analysis (Figure 1 ). The rising trends in NLR and MLR started to happen around 6 months before patient death with a dramatic acceleration approximately 3 months before death. This is accompanied by a rise in CRP. There is an apparent ordered inflammatory response with dialysis vintage with trends being more marked in acute phase patients versus late-stable phase patients (Figure 2 ). Patients who died within the 1 st year on dialysis had the highest neutrophil and monocyte counts, lower levels of lymphocyte count, and consequently higher levels of NLR and MLR in all months preceding to death. Conclusion: The consistent observation of this large observational study that all the inflammatory markers show a similar trajectories in the 6 months anticipating death is remarkable. There is an apparent ordered inflammatory response by era across 4 dialysis vintage groups (acute, early-stable, mid-stable and late-stable phases) which might indicate a pathogenic role for these cell types or be an observed epiphenomena related to survivor advantage for example. This is the first detailed description of increased neutrophil and monocyte counts and notably decreased lymphocyte counts several months before death and possible mechanisms are under investigation.